2013
DOI: 10.1002/hbm.22352
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term neurobiological consequences of early postnatal hCMV‐infection in former preterms

Abstract: Early postnatal infection with human cytomegalovirus (hCMV) may contribute to an adverse cognitive outcome in early preterm-born children (PT). We here set out to explore whether long-term neurobiological consequences of such an infection are detectable using fMRI in children and adolescents who were born very preterm and who either did (PThCMV+ ) or did not (PT(hCMV-)) suffer from an early postnatal hCMV-infection, when compared with typically developing healthy control (HC) subjects. Overall, data from 71 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 114 publications
5
38
0
2
Order By: Relevance
“…This infection entails primary adverse events, such as inflammation, and less specific secondary infectious sequelae, such as hypotension, bradycardia, or apnea. Although overt lesions were equally rare in the 2 preterm groups (both 21%), more sophisticated MRI analyses of our samples indicate that the performance differences might be explained by subtle neural alterations (eg, regional differences in functional activation 15 or disturbances within the neural networks 31 ). Combined with our behavioral data, these findings indicate that the CMV infection may make a difference for the preterm infant's early postnatal brain development.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…This infection entails primary adverse events, such as inflammation, and less specific secondary infectious sequelae, such as hypotension, bradycardia, or apnea. Although overt lesions were equally rare in the 2 preterm groups (both 21%), more sophisticated MRI analyses of our samples indicate that the performance differences might be explained by subtle neural alterations (eg, regional differences in functional activation 15 or disturbances within the neural networks 31 ). Combined with our behavioral data, these findings indicate that the CMV infection may make a difference for the preterm infant's early postnatal brain development.…”
Section: Discussionmentioning
confidence: 72%
“…The entire sample participated in observational studies on neonatal transmission rates, 14,15 and follow-up results of parts of our sample have been previously published, with respect to neurodevelopmental outcome between 2 and 4 years, 10 between 4 and 8 years, 13 and between 6 and 8 years. 14 The current study sample includes children between 11 and 17 years ( Table I) who underwent neuropsychological, neurologic, and magnetic resonance imaging (MRI) examinations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] The majority of prospective and casecontrol studies of postnatal CMV infection among VLBW infants have reported no difference in clinical outcomes, 5-9 although recent studies have found negative impacts on long-term neurodevelopmental outcomes. [10][11][12] Prior studies have included few symptomatic CMV-positive infants, and many asymptomatic, infected infants identified only by prospective screening. 7,9,13 These studies could reassure neonatal clinicians that most instances of postnatal CMV have little impact on VLBW infants.…”
mentioning
confidence: 99%